Physical therapy in patients with Alzheimer’s disease: a systematic review of randomized controlled clinical trials - Marques, Carlos Leonardo Sacomani; Borgato, Maria Helena; Moura Neto, Eduardo De; Bazan, Rodrigo; Luvizutto, Gustavo José (Universidade de São Paulo, 2019)
ABSTRACT The objective of this study is to evaluate the effects of physical therapy on the cognitive and functional capacity of patients with Alzheimer’s Disease (AD). This is a systematic review of randomized or quasi-randomized clinical trials, using the descriptors: AD, dementia and physical therapy. Two studies were included with a total of 207 participants. In study 1, no statistically significant difference was found on the mini-mental state examination (MMSE) (MD 0.0, 95%CI −5.76 to 5.76), neuropsychiatric inventory (MD −4.50, 95%CI −21.24 to 12.24) and Pfeffer instrumental activities questionnaire (MD 0.0 95%CI −6.48 to 6.48). In study 2, there was no statistically significant difference on the MMSE (MD −1.60, 95% CI −3.57 to 0.37), clock-drawing test (MD −0.20, 95%CI −0.61 to 0.21) and Alzheimer’s Disease Assessment Scale - cognitive subscale (MD 1.0, 95%CI −2.21 to 4.21) after 12 months. There was no consistent evidence on the effectiveness of physiotherapeutic intervention in improving cognitive function and functional capacity of patients with AD. More studies should be conducted for better evidence.

RESUMEN El presente estudio tiene como objetivo evaluar los efectos de la fisioterapia en la capacidad cognitiva y funcional de pacientes con enfermedad de Alzheimer (EA). Se trata de una revisión sistemática de ensayos clínicos aleatorizados o casi-aleatorizados, en que se utilizó los descriptores: EA, demencia y fisioterapia. Se incluyeron dos estudios, con un total de 207 participantes. En el Estudio 1, no hubo diferencias estadísticamente significativas en el Miniexamen del estado mental (MEEM) (MD 0,0, IC 95%: 5,6 -5,76), en el inventario neuropsiquiátrico (MD -4,50, IC 95%: 12,24 -21,24) y en el cuestionario de actividades instrumentales de Pfeffer (MD: 0,0 IC 95% IC: -6,48 a 6,48). En el Estudio 2, no hubo diferencias estadísticamente significativas en el MEEM (MD −1,60, IC 95% −3,57 a 0,37), el test de diseño del reloj (MD −0,20, IC 95% −0,61 a 0,21) y la escala de evaluación de la enfermedad de Alzheimer: subítem de cognición (MD 1,0, IC 95% −2,21 a 4,21) tras 12 meses. No hubo evidencia consistente de la eficacia de la intervención fisioterapéutica en la mejora de la función cognitiva y de la capacidad funcional en la EA. Se recomienda realizar estudios adicionales para encontrar posibles evidencias.

RESUMO O objetivo do estudo é avaliar os efeitos da fisioterapia na capacidade cognitiva e funcional de pacientes com doença de Alzheimer (DA). Trata-se de revisão sistemática de ensaios clínicos randomizados ou quasi-randomizados utilizando os descritores: DA, demência e fisioterapia. Dois estudos foram incluídos, com um total de 207 participantes. No Estudo 1, não houve diferença estatisticamente significativa no miniexame do estado mental (MEEM) (MD 0,0, IC 95% 5,76−5,76), inventário neuropsiquiátrico (MD −4,50, IC 95% 12,24−21,24) e questionário de atividades instrumentais Pfeffer (MD 0,0 IC 95% −6,48 a 6,48). No Estudo 2, não houve diferença estatisticamente significativa no MEEM (MD −1,60, IC 95% −3,57 a 0,37), teste do desenho do relógio (MD −0,20, IC95% −0,61 a 0,21) e escala de avaliação da doença de Alzheimer - subitem cognição (MD 1,0, IC95% −2,21 a 4,21) após 12 meses. Não houve evidência consistente da eficácia da intervenção fisioterapêutica na melhora da função cognitiva e capacidade funcional na DA. Recomenda-se a produção de mais estudos para encontrar possíveis evidências.
Fisioterapia en pacientes con enfermedad de Alzheimer: una revisión sistemática de ensayos clínicos aleatorizados controlados
Fisioterapia em pacientes com doença de Alzheimer: uma revisão sistemática de ensaios clínicos randomizados controlados
Keywords: Alzheimer’s Disease; Cognition; Activities of Daily Life; Physical Therapy; Systematic Review; Doença de Alzheimer; Cognição; Atividades da Vida Diária; Fisioterapia; Revisão Sistemática; Ensaios Clínicos